2014
DOI: 10.1159/000358203
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis Hypotension: A Role for Inadequate Increase in Arginine Vasopressin Levels? A Systematic Literature Review and Meta-Analysis

Abstract: Background: Intradialytic hypotension is a common complication of hemodialysis (HD). Some studies have suggested that inadequate arginine vasopressin (AVP) increase could play a role in the pathogenesis of intradialytic hypotension. However, AVP levels during HD and its relation to hypotension has never been systematically studied. Summary: PubMed and Embase were searched (1970-2013, search terms ‘vasopressin' and ‘hemodialysis') for studies reporting on AVP levels during standard HD or other dialysis techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 109 publications
0
22
1
Order By: Relevance
“…10,30,32 The use of blood volume monitoring, a dialysate cool in temperature, the adequate prescription and frequency of dialysis treatments, ultrafiltration profiling, automatic biofeedback-controlled dialysis, and the administration of arginine vasopressin are advocated as tools to reduce hypotension and therefore prevent subsequent NAION. 1416 …”
Section: Discussionmentioning
confidence: 99%
“…10,30,32 The use of blood volume monitoring, a dialysate cool in temperature, the adequate prescription and frequency of dialysis treatments, ultrafiltration profiling, automatic biofeedback-controlled dialysis, and the administration of arginine vasopressin are advocated as tools to reduce hypotension and therefore prevent subsequent NAION. 1416 …”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest is arginine vasopressin, which has potent vasoconstrictor effects via its action on V1a receptors in the vasculature. Under normal conditions arginine vasopressin is stimulated by increases in plasma osmolality and significant hypovolemia; however, these responses appear to be blunted in hypotension-prone patients on hemodialysis (44). Indeed, we previously reported that higher predialysis calculated osmolarity is associated with greater decline in intradialytic BP (4), whereas others have reported on the benefit of infusing vasopressin for the prevention of IDH (44).…”
Section: Arteriolar Vasoconstrictionmentioning
confidence: 99%
“…There are several studies evaluating adequacy and levels of AVP in IDH. Ettema et al also published a meta‐analysis including these studies and determined that there is a little or no increase in AVP during HD sessions in patients with IDH and mentioned that a blunt response could be the one of the pathophysiogical issues in IDH . A possible deficiency of AVP response in IDH also led trials of replacement therapies.…”
Section: Discussionmentioning
confidence: 99%